The vibrations theory of mechanical systems with kinematic excitation and its application to movement of rock handler - Рудь, Ю.С.; Радченко, И.С.; Белоножко, В.Ю.; Ткаченко, А.С. (Eastern-European Journal of Enterprise Technologies, 2010)
Bases of vibrations theory of the mechanical systems are worked out with kinematics excitation, including basic power correlations of vibrations of the mechanical systems, caused by kinematics indignation are certain, found equalization for determination of complete work of force in times of passing of single unevenness of roadway.